Frequency of Acute Mitral Regurgitation in Post Percutaneous Transvenous Mitral Commissurotomy (PTMC) Patients with Severe Mitrall Stenosis (MS) - Amir Saeed, Noor ul Haq, Bilal Mustafa, Muhammad Shahid, Fayaz Ahmed Memon, Fida Muhammad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goal of this study is to see how often Acute Mitral Regurgitation is in patients with severe mitral stenosis who have undergone a percutaneous transvenous mitral commissurotomy (PTMC). Study Design: Cross-sectional study Pace and Duration: The study was carried out at cardiology department of Lady Reading Hospital MTI, Peshawar and PIMS hospital, Islamabad for the duration of six months from 16th August 2021 to 15th February 2021. Methods: A total of 85 patients of both genders that underwent percutaneous transvenous mitral commissurotomy (PTMC) were included in this study. A detailed demographic profile of recruited patients including age, gender and body mass index (BMI) was compiled after obtaining informed written permission from each patient. A technician with over 10 years of experience examined pre- and post-procedure mitral regurgitation using a transthoracic echocardiography (TTE). Frequency of complication was also recorded. SPSS 21.0 was used to analyze all data. Results: Among 85 patients, there were 65 (76.5%) females and 20 (23.5%) males. Mean age of the patients was 39.8 ±9.54 years and mean BMI 24.6±11.42 kg/m2. Previous commissurotomy was found in 9 (10.5%) cases. Pre-operative mean balloon size 26.5±1.88 and mitral valve area was 1.1±0.32. Frequency of severe mitral regurgitation found in 15 (17.6%) cases. 75 (88.2%) patients had no previous history of commissurotomy and the majority were females. Among 9 cases of severe MR, 4 (44.4%) had no previous history of commissurotomy. Conclusion: According to our study, few PTMC patients had significant mitral regurgitation. Procedure is safe and effective. A multiethnic, multicenter, multicity research is proposed in Pakistan to evaluate genetic, environmental, and hospital-related variables associated with post-procedural problems in patients with severe mitral regurgitation who received PTMC.